2018
DOI: 10.1016/j.apmr.2018.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence Treatment After Traumatic Brain Injury: A Multicenter, Randomized Controlled Trial of Interactive Group Treatment Versus Noninteractive Treatment

Abstract: Social competence skills improved for persons with TBI in both treatment conditions. The group interactive format was not found to be a superior method of treatment delivery in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…The LCQ35 (self-report) will be employed as the primary outcome measure in the present RCT. Both Braden et al 26 and Harrison-Felix et al ,25 found the LCQ to be sensitive to change in social communication skills, and comparable with changes found in Social Communication Skills Questionnaire–Adapted (SCSQ-A) used as primary outcome measures in other GIST trials 26. The LCQ has been psychometrically evaluated with excellent results in the TBI population,35 39 40 and it has been translated into Norwegian.…”
Section: Methods and Analysismentioning
confidence: 82%
See 3 more Smart Citations
“…The LCQ35 (self-report) will be employed as the primary outcome measure in the present RCT. Both Braden et al 26 and Harrison-Felix et al ,25 found the LCQ to be sensitive to change in social communication skills, and comparable with changes found in Social Communication Skills Questionnaire–Adapted (SCSQ-A) used as primary outcome measures in other GIST trials 26. The LCQ has been psychometrically evaluated with excellent results in the TBI population,35 39 40 and it has been translated into Norwegian.…”
Section: Methods and Analysismentioning
confidence: 82%
“…To the authors’ knowledge, these are the most recent systematic reviews describing SCD interventions, and a search of Ovid MEDLINE in April 2019 indicated that only four studies have been conducted since 2013. These four studies22–25 provide further evidence for the efficacy of SCD interventions.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…40,41 There has been extensive research into social and community integration after TBI, including return to employment, 7 driving, 8 social participation, 6 and changes in life roles. 42 Programs such as social competence training 43 were designed to improve social skills to broadly facilitate social and community integration. Vocational rehabilitation is designed for the express purpose of providing resources for individuals with TBI to navigate the many complex factors associated with returning to work after injury.…”
Section: Discussionmentioning
confidence: 99%